Fully-coupled and decoupled analysis comparisons of dynamic characteristics of floating offshore wind turbine drivetrain. (1st March 2022) - Yu, Zhiling; Zhu, Caichao; Tan, Jianjun; Song, Chaosheng; Wang, Ye
Abstract: This paper studies the fully-coupled dynamic modeling of the floating offshore wind turbine drivetrain (FOWTD) and discusses its boundary condition setting for the decoupled drivetrain analysis to improve decoupled simulation efficiency and accuracy. Based on the combined wind-wave-current complex environmental loads, a dynamic model of FOWTD coupled with aerodynamic, hydrodynamic, and mooring line modules is established and then verified. Four boundary condition settings including nacelle motions, rotor inertia, mainshaft tilt angle, and rotor mass are employed for the decoupled analysis. Dynamic response differences between fully-coupled and decoupled FOWTD models are compared to determine which decoupled boundary setting has the highest accuracy. The simulation results indicate that setting rotor inertia and mainshaft tilt angle could reduce dynamic load differences between fully-coupled and decoupled FOWTD models while adding nacelle motions could improve the accuracy of gear displacements in the decoupled FOWTD model. However, setting rotor mass at the hub would overestimate the dynamic loads of the decoupled FOWTD model. Highlights: A fully-coupled dynamic model of the floating offshore wind turbine drivetrain is proposed and verified. Dynamic responses of the fully-coupled drivetrain are analyzed under different environmental conditions. The optimal boundary conditions of the decoupled drivetrain are investigated.